The faulty feet of an emerald parrot - Leeuwen, Suzanne van 1981- (2023)
Suzanne van Leeuwen presents a jewel in the shape of a parrot, consisting of two emeralds adorned with diamonds, made around 1600. The maker had many examples within reach at that time, but the details make it clear that this jewel was not crafted to resemble a living bird.
Keywords: Rijksmuseum -- Amsterdam; Geschichte 1580-1620; Sammlung; Smaragd; Diamant; Papageien